Translation Process Strategies: Psycholinguistic Aspects - Леонід Черноватий; Наталія Ковальчук (Психолінгвістика, 2020)
The aim of the paper deals with the preliminary verification of the hypothesis concerning the impact of the source text structure on the choice of translation strategy (form-oriented or sense-oriented) in the process of rendering a text in a native (Ukrainian) into a foreign (English) language by university students majoring in Translation.